The potential of barley straw as an algal and cyanobacterial growth control - Murray, Daniel (Cranfield University, 2009)
Algal and cyanobacterial1 blooms are increasingly becoming a problem to water utilities in the UK and around the world. Conditions such as increasing eutrophication and poor management of water bodies are consequently leading to increases in the number and severity of algal bloom events. These blooms present serious issues to both utilities and the environment; problems include deoxygentation of water bodies leading to fish kill and rapid algal growth leads to overgrowing of other plant species in the water, while blooms of toxic cyanobacteria can lead to the closure of reservoirs and a number of algae can lead to pump and filter blockages in treatment works. The problems created by algal and cyanobacterial blooms are becoming increasingly expensive to offset and while some technologies such as dissolved air flotation exist to control them at treatment level, there are few effective options to tackle blooms where control would be most effective, at the source. What methods there are for source control are often unreliable or almost as bad for the environment as the blooms themselves such as, in the use of chemical pesticides. Barley straw has been shown to have to potential to be an effective control of algal and cyanobacterial blooms at the reservoir level, being able to inhibit a variety of species at practical straw concentrations, but little is known about how it functions or how its ‘effect’ is developed. This study identified spcific areas which when investigated provided insight into these gaps in current knowledge. An analysis of the chemicals proposed as released by decaying barley straw has shown that they can control algal blooms at concentrations similar to what has been detected in the field. Investigations into the decay of barley straw has shown that barley straw decays in water in a way consistent with species that breakdown the lignin section of the straw potentially releasing the proposed chemicals. This finding was supported by the effect being consistent when field rotted straw, fresh straw rotted in the lab, and straw cultured in the lab with species specifically adapted to breaking down the lignin section of the straw were compared. Attempts at pre-treating the straw have shown that microbiological activity is important in developing the algistatic effect, which could lead to the possibility of keeping straw ‘ready for use’ thus removing the current need of several months wait before barley becomes effective. These findings have also provided a definitive route by which barley straw develops its effect, namely, microbiological decay of the lignin fraction of the straw leading to the production of phenol chemical release.